Identification of ageing biomarkers in human dermis biopsies by thermal analysis (DSC) combined with Fourier transform infrared spectroscopy (FTIR/ATR). Issue 4 (17th May 2017) - Tang, R.; Samouillan, V.; Dandurand, J.; Lacabanne, C.; Lacoste‐Ferre, M‐H.; Bogdanowicz, P.; Bianchi, P.; Villaret, A.; Nadal‐Wollbold, F.
Abstract : Background/purpose: The purpose of this clinical study was to identify suitable biomarkers for a better understanding of the molecular and organizational changes in human dermis during intrinsic and extrinsic ageing. Methods: Sun‐exposed and non‐exposed skin biopsies were collected from twenty‐eight women devised in two groups (20‐30 and ≥60 years old). The hydric organization and thermal transitions were determined by Differential Scanning Calorimetry (DSC). Fourier Transform Infrared spectroscopy (FTIR) was used to identify the absorption bands of the dermis and to quantify the different absorbance ratio. Results: The amounts of total, freezable and unfreezable water were determined. A significant increasing amount of freezable water is evidenced in sun‐exposed area skin of aged group compared with young group ( P =.0126). Another significant effect of extrinsic ageing ( P =.0489) is the drastic decrease of fibrillary collagen, the main protein component of dermis. The only significant effect of intrinsic ageing ( P =.0184) is an increase of the heat‐stable fraction of collagens in dermis. Conclusion: DSC and FTIR are well‐suited techniques to characterize human skin, giving accurate results with a high reproducibility. The combination of these techniques is useful for a better understanding of human skin modifications with intrinsic and extrinsic ageing.